Problematic Elementary School Teachers in The Process of Learning Mathematics Online during covid-19 Pandemic - Andriyono, Andriyono; Herman, Tatang (International Conference on Elementary Education, 2021)
The problem that arises in teaching mathematics in the time of the covid-19 pandemic needs to be a concern. Learning is not only the responsibility of the teacher, the role of parents very important in helping students do online learning. This research was conducted to look at the obstacles faced by elementary school teachers while doing online math learning during the COVID-19 Pandemic. Furthermore, this study reveals what factors can be inhibited or support the process of learning mathematics during the COVID-19 pandemic. The method used in this study is qualitative descriptive by providing questionnaires and conducting interviews. The subject of this study was an elementary school teacher in the dukupuntang sub-district of the Cirebon regency. The results of this study show that in general elementary school teachers are not ready to do digital learning. Another obstacle that hinders the learning process is the lack of understanding of teachers and students regarding the use of distance learning applications. So, the government support that has helped ease the burden of internet quotas by subsidizing free quotas to teachers, students and the availability of Wi-Fi in some areas does not seem to be able to maximize used to for online learning.